(untitled) (Jurnal Matematika, Statistika dan Komputasi, 2026)
Quality education is one of the goals of the Sustainable Development Goals (SDGs) aimed at improving human resources. According to the March 2023 Susenas, participation at the college level has the lowest Gross Enrollment Rate (GER), and Kepulauan Bangka Belitung Province has the lowest GER at the college level in Indonesia. The March 2023 Susenas data indicates that four of the seven districts and cities in Kepulauan Bangka Belitung Province still have estimated GER values at the college level with insufficient precision. Therefore, to increase precision, indirect small area estimation (SAE) methods are required using auxiliary variables derived from Podes 2021. The research results show that SAE Hierarchical Bayes (HB) estimation using the beta distribution approach produces the best estimates compared to other methods for estimating GER at the college level.